Educators' perspectives on children's agency in foreign language early childhood education and care - Dimitrova, Tsvetelina (2020)
The topic of children's agency has gained attention since the ratification of the UN Convention on the rights of the child (1989). Internationally, it has been widely studied and in various contexts, among which education. In the Finnish National core curriculum for early childhood education and care (2019) importance is placed on the child as being ‘heard, seen, noticed and understood as himself or herself and as a member of his or her community’ (p. 27). Previous studies in Finland recognizes that, despite policy and educators' efforts, children's agency is often challenging in practice. The purpose of this study is to investigate educators' perspectives of children's agency in foreign language early childhood education and care settings (ECEC). Contrary to most previous studies, here the attention is on routine activities. The data for this research was collected through small group interviews with educators from two kindergartens in the Capital area of Finland. The results show the relational nature of agency in ECEC and its dependence on environmental factors. Educators described it as children's strive for a change, characterised by negotiation and shared responsibility with the educators. They also acknowledged the hindering and supporting role the organizational culture had through pedagogy and routines. The results could be used to reflect theory and practice at work.